Hippocampal corticosterone impairs memory consolidation during sleep but improves consolidation in the wake state. Issue 5 (17th March 2014) - Kelemen, Eduard; Bahrendt, Marie; Born, Jan; Inostroza, Marion
ABSTRACT We studied the interaction between glucocorticoid (GC) level and sleep/wake state during memory consolidation. Recent research has accumulated evidence that sleep supports memory consolidation in a unique physiological process, qualitatively distinct from consolidation occurring during wakefulness. This appears particularly true for memories that rely on the hippocampus, a region with abundant expression of GC receptors. Against this backdrop we hypothesized that GC effects on consolidation depend on the brain state, i.e., sleep and wakefulness. Following exploration of two objects in an open field, during 80 min retention periods rats received an intrahippocampal infusion of corticosterone (10 ng) or vehicle while asleep or awake. Then the memory was tested in the hippocampus‐dependent object‐place recognition paradigm. GCs impaired memory consolidation when administered during sleep but improved consolidation during the wake retention interval. Intrahippocampal infusion of GC or sleep/wake manipulations did not alter novel‐object recognition performance that does not require the hippocampus. This work corroborates the notion of distinct consolidation processes occurring in sleep and wakefulnesss, and identifies GCs as a key player controlling distinct hippocampal memory consolidation processes in sleep and wake conditions. © 2014 Wiley Periodicals, Inc.